An improved graph-based visual localization system for indoor mobile robot using newly designed markers. (13th April 2018) - Li, Yuehua; Zhu, Shiqiang; Yu, Yiqi; Wang, Zhi
To address the localization problem for a mobile robot in an indoor environment, an improved visual localization system based on artificial markers is proposed in this article. First, we will present a novel artificial marker which can be detected and identified easily and correctly. We will then introduce how it is designed, recognized, and verified. The markers are arranged on the ceiling and the mobile robot moves around on the ground to capture images with an up-facing monocular camera. The markers' information, including the position and direction, will be obtained by processing the images. The camera's uncertainty model is then put forward based on the distortion of the camera. The uncertainty of the obtained markers' information is analyzed through the uncertainty model. Finally, with the obtained information, the marker map in global image coordinate system is established and optimized through a graph-based algorithm in which the edges can be updated to reduce the uncertainty using Bayes Estimation method. To verify the effectiveness of the localization system, numerous experiments have been conducted. Additionally, the proposed method has also been applied to industrial forklift to test its robustness in a factory environment.